Striking the balance: Life insurance timing and asset allocation in financial planning - An Chen; Giorgio Ferrari; Shihao Zhu (Bielefeld University, Center for Mathematical Economics (IMW), 2023)
This paper investigates the consumption and investment decisions of an individual facing uncertain lifespan and stochastic labor income within a Black-Scholes market framework, A key aspect of our study involves the agent's option to choose when to acquire life insurance for bequest purposes, We examine two scenarios: one with a fixed bequest amount and another with a controlled bequest amount, Applying duality theory and addressing free-boundary problems, we analytically solve both cases, and provide explicit expressions for value functions and optimal strategies in both cases, In the first scenario, where the bequest amount is fixed, distinct outcomes emerge based on different levels of risk aversion parameter γ: (i) the optimal time for life insurance purchase occurs when the agent's wealth surpasses a critical threshold if γ (0,1), or (ii) life insurance should be acquired immediately if γ>1, In contrast, in the second scenario with a controlled bequest amount, regardless of γ values, immediate life insurance purchase proves to be optimal.
urn:nbn:de:0070-pub-29850761
Keywords: G11; E21; I13; 330; Portfolio Optimization; Consumption Planning; Life Insurance; Optimal Stopping; Stochastic Control